1999
DOI: 10.1021/bi990721e
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Exfoliative Toxin B:  A Superantigen with Enzymatic Activity,

Abstract: The exfoliative toxins (ETs) cause staphylococcal scalded skin syndrome, a disease characterized by specific separation of layers of the skin. Evidence suggests that the toxins act as serine proteases, though the specific substrate and mode of action are not known for certain. The crystal structure of exfoliative toxin A (ETA) was reported earlier and shown to be similar to that of the chymotrypsin-like serine proteases. Here, we report the 2.4 A resolution crystal structure of the other exfoliative toxin, ETB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 29 publications
4
47
0
2
Order By: Relevance
“…First, it was hypothesized that the ETs cause epidermolysis as a consequence of direct action at the desmosomes. This is supported by our recent observations that ETs have structures similar to serine protease enzymes (11,30). Furthermore, it has been shown that ETs have esterase activity (Ref.…”
Section: Discussionsupporting
confidence: 76%
“…First, it was hypothesized that the ETs cause epidermolysis as a consequence of direct action at the desmosomes. This is supported by our recent observations that ETs have structures similar to serine protease enzymes (11,30). Furthermore, it has been shown that ETs have esterase activity (Ref.…”
Section: Discussionsupporting
confidence: 76%
“…Epidermolysins were previously considered serine proteases on the basis of sequence homologies and esterase activity (37). This activity was confirmed by structure-function relationship studies (5), but a concurrent rationale of a superantigenic activity (48) was advanced based on the fact that the bacteria were not necessarily found in all the skin bullae observed in SSSS. However, detection of the toxin in these bullae was never undertaken.…”
Section: Discussionmentioning
confidence: 90%
“…Both toxins cause intraepidermal cleavage through the granular layer, without epidermal necrolysis or an inflammatory response of the skin (6,19,27). Several lines of evidence have suggested that ETs act as serine proteases to induce intraepidermal cleavage: (i) amino acid sequences of ETA and ETB show similarity with the S. aureus V8 serine protease (17), and the catalytic site of V8 protease is conserved in ETA (7); (ii) partially purified ETs preincubated with serine protease inhibitors exhibit delayed skin exfoliation (17); (iii) replacement of the serine residue with glycine in the putative catalytic site of ETA completely abolishes the exfoliative activity of the toxin (35,38); and (iv) crystal structures of ETA (13,53) and ETB (52) have recently been determined, and both types were shown to structurally belong to the chymotrypsin family of serine proteases. However, the exact target substrate was a mystery for 30 years, until the pathogenic role of ET was demonstrated in 1970 by using neonatal mice (29).…”
mentioning
confidence: 99%